FORMATION OF MAKING DECISIONS MODEL FOR DISPATCH TASKS OF ELECTRICAL PRODUCTION - Цивінський, К. (Science-based technologies, 2011)
It is presented the logic-linguistic model of supervisory control of electrical production that is among the complex organizational and technical facilities. Describes how her conversion to the canonical form of extreme combinatorial algorithm problems and making management decisions, which implements a strategy of directed enumeration.